If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6g + (-4 + 2g) = 1 + -1g Remove parenthesis around (-4 + 2g) 6g + -4 + 2g = 1 + -1g Reorder the terms: -4 + 6g + 2g = 1 + -1g Combine like terms: 6g + 2g = 8g -4 + 8g = 1 + -1g Solving -4 + 8g = 1 + -1g Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add 'g' to each side of the equation. -4 + 8g + g = 1 + -1g + g Combine like terms: 8g + g = 9g -4 + 9g = 1 + -1g + g Combine like terms: -1g + g = 0 -4 + 9g = 1 + 0 -4 + 9g = 1 Add '4' to each side of the equation. -4 + 4 + 9g = 1 + 4 Combine like terms: -4 + 4 = 0 0 + 9g = 1 + 4 9g = 1 + 4 Combine like terms: 1 + 4 = 5 9g = 5 Divide each side by '9'. g = 0.5555555556 Simplifying g = 0.5555555556
| 4(5+4x)=-31-x | | 3x-(4x+8)=2(16-x) | | P+5p=-12 | | 5x-21=19 | | 2.625(x/8+0.125)=64 | | 4x^2-19x+31=4x+3 | | 14x-8+2x-5=13x-3+2x | | 6(x+2)-(x-3)=3(-x+1) | | X-6=2x-15 | | 4(1-5x)-4=10x | | (2a^3b^3+7ab^2)+(5ab^2-2a^3b^3)= | | 8x+5x=104 | | 7x-2x+9+3x+8-5x+6=5 | | x-3(x-12)=26 | | 5(3x+2)=32.5 | | (x-3)(15-6x)=0 | | 17=2x+8 | | x(2x-5)=8 | | 15x-40+21x+18=48x+18-8x-20 | | ax+2=3x+a | | 4x+4=4y | | 12w^4+56w^3+32w^2=0 | | x^4=-25 | | 5x+13=42 | | 4y+10=46 | | 4u^3w^4+12u^9w^6x^9=0 | | 8.7+3.6-5.3= | | 12-10x=80-38x | | 3(4x+5)(3x-2)=0 | | 6(n+4)=8+7n | | 18d-4d-6d-8=2d | | -5m=4m+8 |